2014
DOI: 10.14814/phy2.12086
|View full text |Cite
|
Sign up to set email alerts
|

Lack of megalin expression in adult human terminal ileum suggests megalin-independent cubilin/amnionless activity during vitamin B12absorption

Abstract: Cubilin plays an essential role in terminal ileum and renal proximal tubules during absorption of vitamin B12 and ligands from the glomerular ultrafiltrate. Cubilin is coexpressed with amnionless, and cubilin and amnionless are mutually dependent on each other for correct processing to the plasma membrane upon synthesis. Patients with defects in either protein suffer from vitamin B12‐malabsorption and in some cases proteinuria. Cubilin lacks a transmembrane region and signals for endocytosis and is dependent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Cubam and megalin co-localise in the endocytic apparatus and appear to be functionally dependent on each other, at least in the kidney 43 , 44 . However, megalin is not required for cubam surface expression 16 and the fact that megalin seems less expressed in the intestine 45 suggests that cubam is capable of functioning independently of megalin. The extraordinary sizes of receptor ecto-domains in both megalin and cubam are remarkable and may be advantageous for optimal catching and endocytosis of multiple ligands from the extracellular fluids.…”
Section: Discussionmentioning
confidence: 99%
“…Cubam and megalin co-localise in the endocytic apparatus and appear to be functionally dependent on each other, at least in the kidney 43 , 44 . However, megalin is not required for cubam surface expression 16 and the fact that megalin seems less expressed in the intestine 45 suggests that cubam is capable of functioning independently of megalin. The extraordinary sizes of receptor ecto-domains in both megalin and cubam are remarkable and may be advantageous for optimal catching and endocytosis of multiple ligands from the extracellular fluids.…”
Section: Discussionmentioning
confidence: 99%
“…Megalin also facilitates endocytosis of the TCR [ 45 ] and TCR knock out mice show a deficit in brain B12 concentrations accompanied by DNA hypomethylation [ 46 ]. A recent study showed that LRP2 is robustly expressed in the distal ileum during fetal and early postnatal development, but is not expressed in adult human ileum [ 47 ], indicating an age-dependent decline in its expression. Thus a decline in megalin and/or TCR activity could underlie the lower brain levels of vitamin B 12 we observed in elderly subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, cubilin may also associate with the protein amnionless, which has been shown to be required for cubilin internalization and transport to the cell surface [178]. A recent study shows that cubilin is expressed in human terminal ileum in the absence of megalin but instead depends on association with amnionless, a finding that strongly suggests that cubilin and amnionless may operate independently of megalin [179]. The functional impact of the these proteins in uptake and transport of albumin at the different body sites and tissues are not well studied, except for its role in reabsorption in the kidneys, as discussed below.…”
Section: Cubilin and Megalin -Multibinding Endocytic Proteins With Afmentioning
confidence: 99%